Anatomy of a Disaster Bazaar de La Charite Fire - Özgüç, Anıl; Bakar, Murat; Oral, Gökhan (The Bulletin of Legal Medicine, 2011)
Bazaar de la Charité was established in order to help and charity in Paris by Catholic French Aristocrats in 1885 and continued to exist until the fire in 1897 as an annual organization. 126 people died in the fire most of them were aristocrats. After the fire 30 dead bodies could not be identified by the relatives and applied the dentists in order to identification. After the examinations carried out by Dr. Oscar Amoedo, they were identified. Dr. Oscar Amoedo established the basis of forensic odontology by publishing an article about the role of dentists in post fire identification and a book called "L'art dentaire en Medecine Legale”Key words: Bazar de la Charite, forensic odontology, fire, Paris
Keywords: bazar de la charite; forensic odontology; fire; paris